Effectiveness of dietary interventions on metabolic and hormonal profiles in women with polycystic ovary syndrome - Mamta Gupta,; Anuradha Yadav, (Asian Journal of Medical Sciences, 2025)
Background: Polycystic ovary syndrome (PCOS) affects women globally and is rising in urban areas due to sedentary lifestyles and unhealthy dietary patterns. It involves hormonal and metabolic disturbances such as insulin resistance and obesity. Lifestyle changes can improve the pathophysiology and symptoms through dietary modifications. However, optimal strategies remain unclear. Aims and Objectives: The present study evaluates the effectiveness of a 12-week dietary intervention on metabolic and hormonal outcomes in women with PCOS. Materials and Methods: This open-label, randomized controlled interventional study was conducted on 59 diagnosed PCOS women after obtaining ethical clearance and written consent. Participants underwent a 12-week dietary intervention based on the Indian Council of Medical Research and National Institute of Nutrition’s Recommended Dietary Allowances. Metabolic and hormonal parameters were recorded at baseline, 6 weeks, and 12 weeks. Results were expressed as mean±standard deviation. Data were analyzed using repeated measures analysis of variance, with Bonferroni post hoc tests for pairwise comparisons, and a P<0.05 was considered statistically significant. Results: Most participants were young, urban, educated, and from higher socioeconomic backgrounds. Dietary modification led to significant reductions in hemoglobinA1c, lipid parameters (triglycerides, total cholesterol, and low-density lipoprotein), and an increase in high-density lipoprotein levels, reflecting improved metabolic health. Hormonal profiles also improved significantly, with reductions in LH, insulin, dehydroepiandrosterone, estradiol, prolactin, and testosterone, and increases in sex hormone binding globulin and progesterone. Conclusions: The findings indicate that structured dietary interventions are effective in improving both metabolic and hormonal parameters in women with PCOS. This highlights the potential of dietary modification as a valuable non-pharmacological approach to managing PCOS-related health issues.